Chief Justice Rose Bird's State of the Judiciary Address at State Bar Annual Meeting - Watkins, Howard::::::::: (1985)
Incoming State Bar President David Heilbron speaking at dais with Chief Justice Rose Bird and outgoing State Bar President Burke Critchfield seated on dais Seal of State Bar of California on lectern